History of Research into the Food and Feeding of Euphausiids - Nemoto, Takahisa (Proceedings of the Royal Society of Edinburgh. Section B. Biology, 1972)
Much attention has been paid to euphausiids or krill because of their value as indispensable food of baleen whales and commercially important fish both in the North Atlantic and North Pacific and more recently attempts to exploit euphausiids for human consumption were undertaken in the Antarctic, North Pacific and in the Norwegian fjords.